1972
DOI: 10.1111/j.1471-4159.1972.tb01386.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Studies of S‐100 Protein During Postnatal Ontogenesis of the Brain of Two Strains of Rats

Abstract: We have studied the dynamics of the appearance of cells reacting positively with anti-S-100 protein antiserum, during postnatal neurocytogenesis in the brain of rats of two strains differing in their susceptibility to sound stimuli. The postnatal time of appearance of cells reacting positively with anti-S-100 protein antiserum was somewhat later in rats susceptible to sound-induced seizures than in sound-resistant rats. These differences concerned mainly the cerebral cortex of 12-day-old rats. By day 21 of pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1976
1976
1993
1993

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…This label may be erroneously taken as a labelling of the neuronal plasma membrane. The observation of Sviridov et al [27] and Haglid et al [13] that neurones whose membrane is damaged give a positive cytoplasmic immunoreaction with anti-SlOO protein immune serum can be explained either as due to the penetration of the antibody in the neurone through the lesion in the membrane [13,27] or as the result of a simultaneous lesion in both plasma mem branes (of the neurone and its astrocytic wrapping) with subsequent leakage of SI00 protein from the astrocytic to the neuronal cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…This label may be erroneously taken as a labelling of the neuronal plasma membrane. The observation of Sviridov et al [27] and Haglid et al [13] that neurones whose membrane is damaged give a positive cytoplasmic immunoreaction with anti-SlOO protein immune serum can be explained either as due to the penetration of the antibody in the neurone through the lesion in the membrane [13,27] or as the result of a simultaneous lesion in both plasma mem branes (of the neurone and its astrocytic wrapping) with subsequent leakage of SI00 protein from the astrocytic to the neuronal cytosol.…”
Section: Discussionmentioning
confidence: 99%
“…However, the immunostaining found only in glial cells in the human retina but not in neurons [7] allows it to be still used as glial marker for the histogenesis study of retino blastoma [2,3,11], However, the presence of the protein in neuronal cells including autono mic ganglia [8,9] and the substantial species variation in the retinal distribution of the pro tein [7] suggest that it is of limited value in investigating the same condition in chicken and human eyes. Molnar et al [10] found im munoreactivity of S-100 protein in the neuron of the chicken retina but not in human retina and indicated how misleading it can be to use the distribution of the protein in one species to generalize the distribution of the same protein in other species.…”
Section: Discussionmentioning
confidence: 99%
“…ical properties of S-100 protein in different cell types in the retina, because of the presence of the protein in the neurons inside and outside of the CNS [8,9] and the variation of the cell types expressing the protein in the retina of animals and human eyes [10,11],…”
mentioning
confidence: 99%
“…The S-100 protein (31) is present in and synthesized by glial cells (22,(2)(3)(4)9,27,12), but its location also in neurons seems by now undisputed (22,37,44,16,18,17). However, controversial views on the neuronal S-100 protein have been presented (33).…”
Section: Introductionmentioning
confidence: 99%